Mantra dhanyang mageri omah: analisis fonologis, morfologi, dan sintaktis dalam perspektif aksiologis - Masitoh, Dewi; Putra, Valdi Giffari Rahmayati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Mantra is an oral tradition that is believed to have mystical powers that can generate forces beyond human comprehension, such as the dhanyang mageri omah mantra practiced in Pagak Hamlet, Cengkok Village, Ngronggot Subdistrict, Nganjuk Regency. The dhanyang Mantra mageri omah is an oral tradition with mystical power, employed to protect homes with the assistance of supernatural beings khown as dhanyang. This research aims to analyze the phonological, morphology, syntax, and function aspects of the Dhanyang Mantra. This study's phonological, morphological, and syntactic analysis was conducted using a descriptive-qualitative approach and observation, interview, and documentation techniques. Findings reveal that the Dhanyang Mantra demonstrates a harmonious blend of phonological elements (such as alliteration, assonance, and imperfect rhyme), morphological (such as free and bound morpheme), and syntactic structures (types of sentences), adhering to principles of structural analysis. Functionally, the dhanyang mantra serves as a conduit for communication with supernatural entities and as an intermediary connecting humans, God, the Prophet Muhammad, and dhanyang spirits. The religious and cultural significance embedded within the dhanyang mantra reinforces the belief of Pagak Hamlet's inhabitants in the protective capabilities of dhanyang. This research contributes to comprehending and preserving cultural heritage and indigenous wisdom within local religious practices.